Manajemen Waktu Dalam Keluarga Sebagai Upaya Meningkatkan Keseimbangan Peran Orang Tua Dan Anak - Aulia Dwi Febriyani; Yani Achdiani (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
In modern family life, parents are often faced with sharing responsibilities, such as work, childcare, education, and household management. This situation demands effective time management so that each family member receives sufficient attention and support. A literature review shows that effective time management plays a crucial role in resolving role conflict. Family support is a key factor in work-life balance, which can directly impact the nutritional needs of early childhood. Good time management can help parents divide roles equitably, improve the quality of interactions with their children, and support their emotional, social, and academic development, both at school and at home. Family support and communication are key to the successful implementation of time management at home. Barriers to time management risk reducing the effectiveness of parents’ role in supporting their children. Family time management is not only related to the efficiency of daily activities, but also forms the basis for creating a balanced, harmonious, and prosperous family.